Utilization of Go-Food Services in Students’ Halal Lifestyle1 - Rahmania Rahman; Hermon. M. Karwur; St. Fathimah; Eka Yuliana Rahman; Sang Putrisidik; Paulus Robert Tuerah (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
In the current era, lifestyle is closely related to the times and technology. Ordinary lifestyle is also said to reflect the whole person who interacts with the environment. The halal lifestyle is currently becoming a global trend, a part of the halal lifestyle is choosing food, go-food services are one of the tools used by most people to buy food, including students. User of go-food services in halal lifestyle of Muslim students in Manado State University. This study aims to determine the use of go-food applications to help students ’halal lifestyle and to determine the inhibiting factors for the use of go-food applications in students’ halal lifestyle. This research is a descriptive qualitative research. The research subjects were Muslim students at Manado State University. Data collection methods used were observation, interviews and documentation. The results showed that students with monthly order transactions 2 to 5 times were 16%, students with monthly orders 6 to 10 times were 25%, students with monthly orders 11 to 15 times were 35%, and monthly order transactions more than 15 times were found. 24% of the total respondents. The use of go-food services helps students’ halal lifestyle because go-food services provide many attractive promos, convenience in terms of payment systems, and convenience in ordering without needing to leave the house and being able to reach food places that are far from where students live. and what is an inhibiting factor in the use of go-food services in the halal lifestyle of students, namely the costs incurred are greater when using go-food services than buying directly to the place where the food is sold and some food stores do not include halal labels and many food stores lawyers who have not collaborated with go-food services.